Transitions : making sense of life's changes - Bridges, William (Perseus Books CambridgeUS, 1980)
Provides a 3-stage road map of the transition process. Identifies the 3 stages as: first, ENDINGS; second, the NEUTRAL ZONE which is often characterised by confusion, emptiness, and distress; but if successfully managed, it could lead to the third phase: the NEW BEGINNING. Provides useful strategies for dealing with each stage of life's transitions, and makes effective use of case stories, anecdotes, and classical myths.